STUDI PERBANDINGAN MOTIVASI BELAJAR SISWA KELAS XI JURUSAN IPS DI SMAN 10 PONTIANAK DAN JURUSAN AKUNTANSI DISMKN 1 PONTIANAK - Ranodi Ranodi; Junaidi H. Matsum; Rum Rosyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to determine the differences in the characteristics of student motivation, which will be examined in the form of comparative studies. The number of samples in this study were 30 students of class XI of the Social Sciences Department at SMA N 10 Pontianak and 33 students of class XI of the Department of Accounting at SMK N 1 Pontianak in the comparison of learning motivation using parametric statistics with the formula t test polled variance and independent sample t test in SPSS 16 program for Windows. In this research, it is known that for manual count results using the t test polled variance formula, it is obtained that the results of t count > t table or 0.195 < 1.998 and for independent sample t test in SPSS 16, the results of t count > t table or 0.727 < 1.998. So that the results of the research data indicate that there are no differences in the characteristics of high school and vocational high school students' motivation in their learning motivation. Keywords: Comparative Study, Learning Motivation, Characterirstics